RECOGNITION OF PATTERNS ON FRACTURE SURFACES BY AUTOMATIC IMAGE ANALYSIS - Jacek, Komenda; Barbara, Maroli; Lars, Höglund (Image Analysis and Stereology, 2011)
Image Classifier, the software package integrated with the MicroGOP2000/S system (Sweden), is applied to quantitatively analyse fracture surfaces. After training the system in automatic recognition of different fracture morphologies, measurements of apparent porosity in three sintered steel specimens are performed The results are related to the bending fatigue limits. Automatic recognition is also used to measure the coarseness of fracture surfaces related to the so-called Jernkontoret Fracture Standard Set Number.